Plant Diseases Current Threats and Management Trends - Topolovec-Pintarić, Snježana (IntechOpen, 2020)
Plant pathogens, the causal agent of infectious plant diseases, influence our lives more than just as an economic impact through yield lost. The study of plant pathogens has given rise to the development of new sciences, new technologies for plant breeding, and the agrochemical industry for pesticide developments. Yet, all our actions and efforts to suppress or eradicate them constantly pressures these various organisms to evolve and adapt for survival. Therefore today, when facing climate changes, accelerated transport of plants and plant products, and world population growth, we have to ask quo vadis phytopathology. Like Alice in Wonderland "If we wish to go anywhere we must run twice as fast as that" so we need to constantly broaden our knowledge. However, today's literature abounds with knowledge about plant pathogens. Hence, this book intends to present to the reader all the latest material and knowledge about plant pathogens, changes or refinements in plant disease epidemiology, and new approaches and materials used for plant pathogen control. Hopefully, this book will be of interest to those working within the field and looking for an up-to-date introduction. We hope it also interests students and thereby, will influence the future development of phytopathology and our better coexistence with plant pathogens.